Experimental Inoculation of Conventional Pigs with Porcine Reproductive and Respiratory Syndrome Virus and Porcine Circovirus 2 - Rovira, A. (American Society for Microbiology, 2002)
Postweaning multisystemic wasting syndrome (PMWS) is a disease of nursery and fattening pigs characterized by growth retardation, paleness of the skin, dyspnea, and increased mortality rates. Porcine circovirus 2 (PCV2) has been demonstrated to be the cause of PMWS. However, other factors are needed for full development of the syndrome, and porcine reproductive and respiratory syndrome virus (PRRSV) infection has been suggested to be one of them. Twenty-four conventional 5-week-old pigs were distributed in four groups: control (n = 5), PRRSV inoculated (n = 5), PCV2 inoculated (n = 7), and PRRSV and PCV2 inoculated (n = 7). The two groups inoculated with PRRSV showed growth retardation. Pigs inoculated with both PRRSV and PCV2 had increased rectal temperature. One of these pigs developed wasting, had severe respiratory distress, and died. The most important microscopic lesion in pigs inoculated with PCV2 was lymphocyte depletion with histiocytic infiltration of the lymphoid organs, more severe and in a wider range of tissues in doubly inoculated pigs. Interstitial pneumonia was observed in the three inoculated groups. PCV2 nucleic acid was found by in situ hybridization in larger amounts and in a wider range of lymphoid tissues in PRRSV- and PCV2-inoculated than in PCV2-inoculated pigs. TaqMan PCR was performed to quantify the PCV2 loads in serum during the experiment. PCV2 loads were higher in doubly inoculated pigs than in pigs inoculated with PCV2 alone. These findings indicate that severe disease can be reproduced in conventional 5-week-old pigs by inoculation of PRRSV and PCV2. Moreover, these results support the hypothesis that PRRSV infection enhances PCV2 replication.